2016
DOI: 10.15406/ghoa.2016.04.00111
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection: Association with Hashimoto’s Thyroiditis

Abstract: Autoimmune thyroid diseases (ATDS) are multifactorial conditions that result from genetic predisposition in combination with environmental risk factors. Helicobacter Pylori (HP) infection as an environmental risk factor has been proposed to initiate the antigenic components of the thyroid cell membrane and may play a leading role in the onset of the auto immune diseases such as Hashimoto's thyroiditis (HT).The Aim: To investigate the association between H.P infection and HT and the prevalence of cag. A positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…This could subsequently damage the thyroid tissues, thus increasing the disorder's progression. Our results were consistent and were confirmed by a local study (Aboud, 2011) in addition to other regional and international studies (Aghili et al,2013;Shi et al,2013;Korani et al,2016). Otherwise, Bassi et al concluded that the correlation between H. pylori and autoimmune thyroid diseases was found only with Graves's disease and not Hashimoto's.…”
Section: Discussionsupporting
confidence: 92%
“…This could subsequently damage the thyroid tissues, thus increasing the disorder's progression. Our results were consistent and were confirmed by a local study (Aboud, 2011) in addition to other regional and international studies (Aghili et al,2013;Shi et al,2013;Korani et al,2016). Otherwise, Bassi et al concluded that the correlation between H. pylori and autoimmune thyroid diseases was found only with Graves's disease and not Hashimoto's.…”
Section: Discussionsupporting
confidence: 92%